Conserving roadside populations of Colorado's globally imperiled plants, a pilot project - Smith, Gabrielle, author; Panjabi, Susan Spackman, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
Colorado supports habitat for approximately 120 globally imperiled plant species. These plants are in need of conservation attention to prevent unnecessary extirpations and extinctions. Numerous populations of these globally imperiled plants are known from roadside locations in Colorado. The Colorado Department of Transportation (CDOT), the Colorado Natural Areas Program at Colorado Parks and Wildlife (CPW), and the Colorado Natural Heritage Program (CNHP) are working together to ensure that information about the roadside plant populations is made available to the people and organizations managing and working along the roadways. Location information is critical to communicate so that road crews, weed managers, and others can avoid preventable harm to the plants. Further, there is a need for the development of species-specific Best Management Practices (BMPs) that will articulate and specify on-the-ground management considerations for highly imperiled species (for example, specific times to avoid spraying, mowing, etc.). This pilot project addresses these needs by targeting ten globally imperiled plants that are known from roadside locations in Colorado, by delivering user-friendly location information and species-specific Best Management Practices (BMPs) to pertinent parties, and by engaging in outreach to actively reduce the potential threat from road maintenance.
Prepared for: Colorado Department of Transportation and the Colorado Natural Areas Program.
October 2014.
Keywords: noxious weed management; roadside rare plants; best management practices; imperiled plants; Colorado; plant habitat; species profile